Effect of aromatic rings and substituent on the performance of lithium batteries with rylene imide cathodes - Aher, Jagdish; Graefenstein, Alexander; Deshmukh, Gunvant; Subramani, Kumar; Krueger, Bastian; Haensch, Mareike; Schwenzel, Julian; Krishnamoorthy, Kothandam; Wittstock, Gunther (ChemElectroChem, 2020)
Rylene imides (RIs) are attractive organic battery materials because of the inherent modularity of the molecules. While strong aggregation of RIs is disadvantageous for fast lithium-ion transport in the organic active material, decreasing the solubility of the RIs in battery electrolytes is essential to avoid performance fading. Therefore, the design and synthesis of RIs for lithium batteries is a non-trivial task that must, among other considerations, balance lithium-ion transport in the solid material vs. low solubility by controlling aggregation and packing. We have chosen triphenylamine (TPA) as a substituent which disrupts the aggregation but maintains a low solubility due to increased aromaticity of TPA. We have synthesized three RIs with one, two, and four aromatic units in the core. All of them showed stable specific capacity over 300 charge-discharge cycles. The batteries also showed specific capacities close to their theoretical capacities with 97-99 % coulombic efficiency. The maximum specific energy and specific power were 197 mWh g(-1) and 37 mW g(-1), respectively.
Keywords: lithium-ion batteries; organic cathode material; rylene imides; solubility; triphenylamine

Instabilities as the origin of large-area self-assembled and aligned organic semiconductor nanocrystals - Venugopalan, Vijay; Jain, Bhanprakash; Mahale, Rajashree Y.; Subramani, Kumar; Krishnamoorthy, Kothandam (ACS Applied Electronic Materials, 2022)
Aligned nanocrystals of organic semiconductors (OSCs) are highly desirable for electronic devices and biomedical and photonic applications. Solution-based wet processing routes have the potential to produce aligned nanocrystals over large areas in small time frames. Herein, we demonstrate that by optimizing the hydrodynamic evaporative processes, controlled long-range crystalline assemblies of OSCs can be achieved (longest nanocrystal similar to 3 mm) purely through physical processes: namely, from fingering instabilities. Self-assembly is achieved here without strong noncovalent interactions such as hydrogen-bonding interactions. Experimentally our approach involves just placing a drop of a solution on an inclined substrate. Nanocrystals with widths of 300-800 nm and lengths of millimeters (length/width aspect ratios >10(5)) are formed in less than 2-8 s. A hydrazine chemiresistive sensor based on the aligned crystalline patterns show unprecedented responsivity (similar to 10(-6)), 2 orders greater than those of stick-slip patterns. Finally, experimental parameters that need optimization to achieve nanocrystal patterns are investigated in detail and pointers to fabricate such OSC nanocrystals are provided.
Keywords: aligned fibers; diketopyrrolopyrrole; fingering instability; nanocrystal arrays; naphthalenediimide; organic semiconductors